Superscan: Superiority of xSPECT/CT over OSEM SPECT/CT in bone scans of prostate cancer patients. - Chen, Ew-Jun *; Tan, Teik Hin *; Chew, Ming Tsuey * (Elsevier, 2021)
Prostate cancer is one of the most common cancers affecting men. Bone scan is part of the staging modality commonly used to evaluate bone metastasis. A bone scan with diffused increased skeletal tracer uptake relative to soft tissue, combined with faint renal activity is known as a superscan. However, a primary concern are false negatives associated with bone scans, where diffuse metastasis is indistinguishable on superscans. In this study, we performed xSPECT/CT Bone and standard OSEM SPECT/CT reconstruction algorithm in ten prostate cancer patients with high PSA levels, where they initially seem relatively unremarkable on planar images. All patients with extensive bone metastases showed either relatively unremarkable scans or did not demonstrate the true extent of metastatic burden as seen on planar images. Uptake was further confirmed by the correlative diffuse bone lesions on CT images. Our reports also indicated that xSPECT/CT reconstructed images were far superior in delineating focal areas of osteoblastic bone metastasis, when compared with whole body planar images or SPECT/CT images. The extent of metastatic evidence is delineated with excellent clarification by xSPECT/CT images. We propose that whole body xSPECT/CT image reconstruction, or at least SPECT/CT, should be performed in patients with high PSA levels, along with planar imaging, to improve diagnostic accuracy of bone scans in prostate cancer staging.